Tackling Extended Hospital Stays in Patients with Acute Bacterial Skin and Skin Structure Infections - Gavin Barlow; Michael Wilke; Guillaume Béraud (European Medical Journal)
Hospitalisation rates for acute bacterial skin and skin structure infection (ABSSSI) are rising and represent a large pharmacoeconomic burden as treatment may involve an extended number of days of antibiotic therapy. This article first aims to provide a review of treatment challenges associated with ABSSSIs in both hospital and outpatient settings, and shows that while more traditionally treatment has been conducted in a hospital setting, for a number of patients, a variety of considerations, including pharmacoeconomics, infection control, and patient preference, has led to the development of recommendations to assess the eligibility of patients for early discharge from hospital to complete their antibiotic regimen in the outpatient setting. However, such patients require monitoring for drug adherence to oral regimens or complications associated with daily intravenous administration, such as injection site reactions and infection. This review also focuses on one of a number of new antibiotics for ABSSSI, dalbavancin, as the long-acting glycopeptide with the most clinical experience to date. This antibiotic has been shown to be as effective as a daily/twice daily regimen with similar safety profiles. Health economic analysis of dalbavancin is also presented. It has shown that in some, though not all, clinical settings a reduction in the overall treatment cost is evident as, despite a higher medication cost, the lower hospitalisation time can lead to greater cost savings. In conclusion, while the burden of ABSSSI is rising, new treatment options provide additional therapeutic choice, although pharmacoeconomic considerations might limit use in some cases.